The effect of multi-dimensional performance measurement system on market orientation - Mohamed, Rapiah (International Association of Computer Science and Information Technology Press (IACSIT Press), 2014)
The objective of this study is to examine the effect of performance measurement system design on market orientation behavior.The data were collected using mail survey to top management of Malaysian listed companies.The results show that non-financial measures have a positive and significant relationship with market orientation.An implication of these findings is that the managers should include both financial and non-financial measures in designing their PMS.Theoretically, this study contributes to the resource-based theory by identifying PMS as an antecedent to build market orientation and thus contribute to develop an organizational competitive advantage.